2022
DOI: 10.1186/s40792-022-01380-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-view totally extraperitoneal repair in a patient with incisional hernia after robot-assisted laparoscopic radical prostatectomy: a case report

Abstract: Background Although laparoscopic incisional hernia repair, especially laparoscopic intraperitoneal onlay mesh, is a widely used technique, it can cause serious complications, including mesh erosion, adhesive bowel obstruction, and chronic pain. The enhanced-view totally extraperitoneal (eTEP) technique has been reported to prevent such complications by placing the mesh in the retrorectus space. Here, we report the case of a patient with post-robot-assisted laparoscopic radical prostatectomy (RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Other reported SSOs include (1) dehiscence of the plicated linea alba/anterior fascia resulting in upper abdominal bulging and (2) disruption of the PRS/peritoneum resulting in bowel herniation and/or obstruction. 8,17,25,26 The first randomized controlled trial (RCT) in 2022 comparing eTEP (30) and IPOM (30) for ventral hernia showed that the former was more cost-effective and associated with lower seroma rates, postoperative pain scores, and earlier return to activity. 27 In 2023, another RCT (29 eTEP vs. 27 IPOM) also showed lower postoperative pain scores with eTEP but was associated with higher surgeons' workload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reported SSOs include (1) dehiscence of the plicated linea alba/anterior fascia resulting in upper abdominal bulging and (2) disruption of the PRS/peritoneum resulting in bowel herniation and/or obstruction. 8,17,25,26 The first randomized controlled trial (RCT) in 2022 comparing eTEP (30) and IPOM (30) for ventral hernia showed that the former was more cost-effective and associated with lower seroma rates, postoperative pain scores, and earlier return to activity. 27 In 2023, another RCT (29 eTEP vs. 27 IPOM) also showed lower postoperative pain scores with eTEP but was associated with higher surgeons' workload.…”
Section: Discussionmentioning
confidence: 99%
“…Treating hernia recurrences after a retromuscular dissection and/or TAR is technically challenging and should be performed in experienced/high‐volume centers. Other reported SSOs include (1) dehiscence of the plicated linea alba/anterior fascia resulting in upper abdominal bulging and (2) disruption of the PRS/peritoneum resulting in bowel herniation and/or obstruction 8,17,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…2 shows a schema of the endoscopic port placement in this case. The eTEP repair was performed as previously described [ 9 ]. The preperitoneal and bilateral retrorectus spaces were created from the cranial to the caudal direction by incising the bilateral posterior rectus sheaths.…”
Section: Case Presentationmentioning
confidence: 99%